2018
DOI: 10.13005/ojc/340657
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Mass Spectrum Characterization of Lyrame Schiff Base for Synthetic Ingredients in Perfumes Industry

Abstract: Fragrance was a common material in human daily life. It has unique property, especially in odor. Lyrame was a synthetic precursor that was added to fragrance to increase fragrance stability and make odor last longer. Lyrame can be synthesized by using simple condensation method. This method was effective and low cost. The synthesis of lyrame uses lyral and methyl anthranilate as a precursor. The weighting methyl anthranilate was mixed to lyral solution, then heated and stirred at temperature 110 ± 50C for 30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Aurantiol has the molecular formula C 18 H 27 NO 3 , with a molecular weight of 305.43 g/mol. 16 In the previous study, aurantiol was synthesized with simple condensation at a temperature of about 90 ± 5°C with a time variation for 15, 30, 60, 120, 180, and 240 minute. The results showed that the optimal synthesis time about 30 to 60 min can be used as a reference for aurantiol synthesis in an industrial scale.…”
Section: Brief Communicationmentioning
confidence: 99%
“…Aurantiol has the molecular formula C 18 H 27 NO 3 , with a molecular weight of 305.43 g/mol. 16 In the previous study, aurantiol was synthesized with simple condensation at a temperature of about 90 ± 5°C with a time variation for 15, 30, 60, 120, 180, and 240 minute. The results showed that the optimal synthesis time about 30 to 60 min can be used as a reference for aurantiol synthesis in an industrial scale.…”
Section: Brief Communicationmentioning
confidence: 99%
“…MA is a prevalent flavor additive in candy, gum, soft drinks, and alcoholic beverages ( Luo et al ., 2019 ). Additionally, MA is utilized as a bird repellent in agriculture ( Bernklau et al ., 2019 ), and as an ingredient in medicines and perfumes ( Irawan et al ., 2018 ). In this study, we investigated the potential of MA as a novel skin brightening agent.…”
Section: Introductionmentioning
confidence: 99%
“…Schiff base is able to increase the chemical and temperature stability from fragrances. 14 Several schiff bases have been using in fragrance industry such as Jasmea, Cyclantine, Indolen, Vertosine, Agrea, Decimea, Nonimea, Ocmea, Isonomilat 258 E, Amandolen, Canthoxalia, Acaciol, Aurantiol, Lyrame and verdantiol 14,15,16 . Verdantiol is produced by condensation reaction of Lilyall and methyl anthranilate 14 .…”
Section: Introductionmentioning
confidence: 99%